The Fama-French Three Factor Model Test on Excess Stock Return: Evidence From Hong Kong, Indonesia and Singapore Capital Market - Silfia, Silfia; Husodo, Zaafri A (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The presence of the capital market has a very important role in the world economy because the capital market carries out economic and financial functions. One of the instruments in the capital market is stock. In stock investment, investors expect a return with a size that is in accordance with the level of risk they can afford. This study wants to test whether the Fama-French Three Factor Model variables, namely market excess returns, book-to-market equity and firm size, can be used to explain excess returns on the stock markets of Hong Kong and Indonesia with the observation period of 2018–2022. Based on the test results multiple linear regression, Gibbons, Ross, and Shanken test (GRS test) and spanning test, this study found that the variables in the Fama-French Three Factor Model can simultaneously be used to explain the excess return on all stock portfolios on the stock market in Hong Kong and Indonesia, and can only be used to explain the excess return on Big and S-H portfolios in Singapore. Based on the results of the GRS-test, in the Hong Kong market the most efficient portfolio is S-M, in the Indonesian market the most efficient portfolio is the Big portfolio, while in the Singapore market all portfolios are efficient and based on the spanning test, in the Hong Kong market the potential redundant factor is SMB, in in the Indonesian market, the potential redundant factor is HML, while in the Singapore market, there is no redundant potential factor.